Peningkatan Penalaran Matematika Melalui Strategi Pembelajaran Problem Based Learning Pada Siswa Kelas Vii I Semester Ganjil Mts Negeri Surakarta Ii Tahun 2015/2016 - Pratiwi, Erlinda Dihan (2016)
This study aimed to describe the increased reasoning for students learning math class VII I MTs Negeri Surakarta II with learning strategy problem based learning. This study uses a classroom action research. Source data comes from teachers and students. Implementation of a class action carried out during two cycles consisting of 4 meetings. Methods of data collection is done through tests, observations, field notes, interviews and documentation. Data analysis techniques used by qualitative descriptive through three stages of data reduction, exposure data, and inference. Validity of data with triangulation of methods and sources. Results of the study, the first application of learning strategy problem based learning can improve students' mathematics learning reasoning MTs Surakarta VII I class II. Both the increase in the reasoning of learning mathematics, namely 1) the student is able to pronouncement serve the initial conditions (40.00%), in the first cycle (50.00%), and the second cycle (77.50%), 2) the student is able to proof arranged or gifted reason about truth solution of the initial conditions (32.50%), in the first cycle (45.00%), and the second cycle (70.00%), 3) the students is able ability to draw conclusion the initial conditions ( 27.50%), in the first cycle (40.00%), and the second cycle (67.50%). Based on the description above concluded that learning with application problem based learning strategies can increase the reasoning of learning mathematics.